Does cultural differences affect merger performance? A study of mergers of equal in United States - Choong, Anne-Marie Wei Lin (2011)
This paper studies the effect of cultural differences between target and acquirer on merger performance among mergers of equal in US. Given that past literature has two schools of thought on whether greater cultural differences lead to poorer firm performance, we attempt to reconcile these conflicting perspectives using differences in degree of religiosity as a proxy for cultural differences. In our sample of 85 mergers of equal, we find no conclusive relation between cultural differences and merger performance. We recommend future research to control for selection effects and sample size issues in order to re-examine the relation between cultural differences and merger performance.